Estimating Allele Frequency from Next-Generation Sequencing of Pooled Mitochondrial DNA Samples - Wang, Tao; Pradhan, Kith; Ye, Kenny; Wong, Lee-jun; Rohan, Thomas E. (Frontiers in Genetics, 2011)
Background: Both common and rare mitochondrial DNA (mtDNA) variants may contribute to genetic susceptibility to some complex human diseases. Next-generation sequencing of pooled mtDNA samples may represent an cost-effective approach for large-scale genetic epidemiology studies. However, the performance of the different designs of sequencing pooled mtDNA has not been evaluated. Methods: We examined the approach of sequencing pooled mtDNA of multiple individuals for estimating allele frequency using the Illumina Genome Analyzer (GA) II sequencing system. In this study the pool included mtDNA samples of 20 subjects that had been sequenced previously using Sanger sequencing. Each pool was replicated once to assess variation of the sequencing error between pools. To evaluate the effect of different pooling strategies pooling was done at both the pre- and post-PCR amplification step. Results: The sequencing error rate was close to that expected based on the Phred score. However, there was significant variation of the base-calling errors for different types of bases or at different loci. Among a total of 298 variants in the sample, the allele frequencies of 293 variants (98%) were correctly estimated with post-PCR pooling, the correlation between the estimated and the true allele frequencies being >0.99, while only 206 allele frequencies (69%) were correctly estimated in the pre-PCR pooling, the correlation being 0.89. Conclusion: Sequencing of mtDNA pooled after PCR amplification is a viable tool for screening mitochondrial variants potentially related to human diseases.